1992
DOI: 10.1002/cyto.990130503
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random distribution of abnormal mitoses in heteroploid cell lines

Abstract: We have performed absorption-cytometric DNA measurements of the DNA contents of the GdG,, G,, metaphase, and telophase cells of the heteroploid MCa-11 and HL-60 lines, as well as the WCHE-5 line which has a narrowly restricted number of chromosomes. We found that morphologically unbalanced mitoses occurred much more frequently in telophase-cell pairs of the heteroploid MCa-11 and HL-60 lines than in those of the chromosomally stable WCHE-5 line. Furthermore, the morphologically unbalanced mitoses represented u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…In several earlier publications supporting this concept it was suggested that heteroploid cells with non-modal DNA contents were destroyed at mitosis and did not reach telophase (Hsu & Moorhead 1956, Stich 1959, Stich & Steel 1962a. In contrast to these results, recent studies in our laboratory have shown the presence of significant proportions of telophase cells with non-modal DNA contents in several heteroploid cell populations (Dooley & Allison 1991, Dooley & Allison 1992.…”
Section: Discussioncontrasting
confidence: 82%
“…In several earlier publications supporting this concept it was suggested that heteroploid cells with non-modal DNA contents were destroyed at mitosis and did not reach telophase (Hsu & Moorhead 1956, Stich 1959, Stich & Steel 1962a. In contrast to these results, recent studies in our laboratory have shown the presence of significant proportions of telophase cells with non-modal DNA contents in several heteroploid cell populations (Dooley & Allison 1991, Dooley & Allison 1992.…”
Section: Discussioncontrasting
confidence: 82%
“…Endoreduplicated cells were seen at low frequency (1-3%), but only in the inducible Ha-ras cells after exposure to IPITG. It has been noted that tumor cells with divergent karyotypes eventually achieve a modal but aneuploid chromosome or DNA content (36), suggesting that there may be a selective pressure for cells to revert to genetic stability. In contrast to G5 cells, 242 cells had been in extended culture for sufficient time to select for mutations that suppress genomic instability but not the transformed phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The authors proposed that this process allows the nonmodal cells to contribute continuously to the genetic diversity of the modal peak. 38 A subsequent study demonstrated that nonmodal cells were capable of continued cell proliferation but were delayed temporarily in the G 2 and/or the prophase-metaphase stages of the cell cycle relative to cells with a modal DNA content. 39 Our data support this hypothesis in that the informational content of the diploid or pseudo-diploid cells of the tumorigenic populations obviously differs from that of the diploid cells of the nontumorigenic founding population of WB-F344 cells.…”
Section: Discussionmentioning
confidence: 99%